MARGov - setting the ground for the governance of marine protected areas - Vasconcelos, Lia (2018)
Started in 2008, the MARGov project proposes to build a Model of Collaborative Governance for Marine Protected Areas (MPA), using as a case study the Marine Park Luiz Saldanha (MPLS), Sesimbra, Portugal. The project works through an eco-social dialogue supported by active participation and aims to empower the local communities making them active agents for the sustainable governance of the coast and the ocean. In fact, successful MPA depend on the balance between man and environment, and on the eco-social dialogue established among all actors. The MARGov project is structured in three components - Governance, Citizenship and Dynamic-Spatial Structure. Here we present the work already developed in two of the components - Governance and Citizenship. The first component mainly aims at reinforcing competences and the co-responsibility of all key-actors within MPLS. Several participatory sessions, involving the local community, have been organized since the end of 2009 improving the communication and to set up a constructive dialog - reducing sources of conflict - among all the stakeholders. The Citizenship component targeted to re-establish the traditional affective link between the local community and the ocean, mostly by means of environmental education sessions in elementary schools. In this paper we present the methodology, the main results and discuss the lessons learned, theorizing from action and exploring how to pursue in the future for the sustainable management of Portuguese MPA. Intermediate outcomes include specific actions (e.g., strategy to promote sustainable tourism, enhance co-liability of users in inspection and surveillance); as well as comprehensive ones, such as a proposal to expand the existing strategic council of the MPA towards a satellite structure of co-management that includes representatives of different stakeholder groups in continuing articulation. The methodology developed for the collaborative process as, so far, revealed to have a substantial potential in enhancing trust building and empowerment. Stakeholders now show greater autonomy to pursue independent initiatives within the social network consolidated during the project.